The Method of the Minimum Area of Alarm for Earthquake Magnitude Prediction - Gitis, Valeri; Derendyaev, Alexander (Frontiers in Earth Science, 2020)
An approach for the systematic forecasting of earthquake magnitudes is considered. To solve this problem, we use the minimum area of alarm method. Testing the approach for Kamchatka and the Aegean Region shows a satisfactory quality of the forecast of earthquakes and their magnitudes.